RESISTIRE D4.3 Summary report on qualitative indicators - cycle 3 ... - Sandström, Lina; Callerstig, Anne-Charlott; Strid, Sofia; Lionello, Lorenzo; Rossetti, Federica (Zenodo, 2023)
The aim of RESISTIRÉ is to understand the unequal impacts of the COVID-19 outbreak and its policy and societal responses on behavioural, social and economic inequalities and to work towards individual and societal resilience. RESISTIRÉ does so by collecting and analysing policy data, quantitative data and qualitative data in the EU27 (except Malta), Iceland, Serbia, Turkey and the UK, and translating these into insights to be used for designing, devising and piloting solutions for improved policies and social innovations, which in turn can be deployed by policymakers, stakeholders and actors in the field across different policy domains. The project relies on an eleven-partner multidisciplinary and multisectoral European consortium and a well-established network of researchers in 30 countries. Throughout the course of RESISTIRÉ, research conducted consistently show how already vulnerable and marginalised groups have become even more vulnerable and marginalised; existing inequalities have increased, and new ...